Hierarchy of Epstein-Barr virus-specific cytotoxic T-cell responses in individuals carrying different subtypes of an HLA allele: implications for epitope-based antiviral vaccines. - Khanna, R (1997)
Major histocompatibility complex class I-restricted Epstein-Barr virus (EBV)-specific cytotoxic T lymphocytes (CTLs) in healthy virus carriers constitute a primary effector arm of the immune system in controlling the proliferation of virus-infected B cells in vivo. These CTLs generally recognize target epitopes included within the latent antigens of the virus. For example, CTLs from HLA B44+ healthy virus carriers often recognize peptide EENLLDFVRF [corrected] from EBV nuclear antigen 6. However, the strength of this response directly correlates with the HLA B44 subtype expressed by the individual donor. Indeed, HLA B*4405+ virus carriers consistently show a very high frequency of CTL precursors for the EENLLDFVRF [corrected] epitope, while a much weaker response is seen in HLA B*4403+ and HLA B*4402+ individuals. This disparity is not due to an intrinsic difference in the CTLs generated by individuals carrying different subtypes of HLA B44. In fact, virus-specific CTLs recognize EENLLDFVRF [corrected] peptide-sensitized HLA B*4405+ target cells more efficiently than B*4402+ or B*4403+ target cells irrespective of the HLA B44 subtype expressed by the donors from whom these effectors were isolated. This effect is evident whether the CTL epitope is endogenously processed or exogenously presented. In addition, a comparison of the intracellular transport kinetics of different B44 subtypes revealed that the B*4405 allele is rapidly assembled and arrives in the trans-Golgi compartment at a faster rate than B*4402 or B*4403. Based on these results, we propose that HLA class I alleles that are capable of binding peptides more efficiently from the intracellular pool, and are rapidly assembled and transported, may confer a protective advantage against viral infection.